A new insight on the role of 1-D and 2-D reinforcements in TiC during high temperature plastic deformation. Issue 15 (15th October 2018) - Sribalaji, M.; Singh, Davinder; Singh, Swarnima; Islam, Aminul; Pandey, Mayank Kumar; Viswanath, B.; Keshri, Anup Kumar
Abstract: Spark plasma sintering (SPS) technique was used to consolidate spray dried (SD) powder of TiC (T-SD), TiC-3.5 wt% WC (TW-SD) and TiC-3.5 wt% WC-2 wt% CNT (TWC-SD) at 1600 °C and 50 MPa pressure. Another, similar composition of ball milled (BM) powder of TiC-3.5 wt% WC-2 wt% CNT (TWC-BM) was consolidated by SPS technique at similar parameters, in which in-situ formation of 2-D graphene nanoribbons (GNR) was observed. High temperature plastic deformation (HTPD) behaviours of these four pellets were characterized by in-situ high temperature nanoindentation technique from RT to 650 °C in controlled atmosphere. Occurrence of HTPD was confirmed by analyzing the mechanical properties, plasticity index and plastic deformation zone radius of all four pellets from RT to 650 °C. The structural stability of 1-D CNTs in TWC-SD and 2-D in-situ formed GNRs in TWC-BM pellets was examined by Raman spectra after the HTPD at 650 °C. HR-TEM micrograph has inferred the collapse of CNT edges in TWC-SD pellet and the peeling of GNR layers in TWC-BM pellet after HTPD. However, the CNTs in TWC-SD pellet was able to lower down the plastic deformation zone radius formed due to HTPD by 60%, while it was only 20% by in-situ formed GNR in TWC-BM pellet. This was majorly attributed to the difference in stress dissipation mechanisms between CNTs and GNRs. The 1-D CNTs in TWC-SD was found to have axial stress dissipation, while the in-situ formed GNRs in TWC-BM pellet has dissipated the stresses in axial as well as transverse directions because of its 2-D nature.